IMPROVING WATER SANITATION AND ITS IMPACT ON PUBLIC HEALTH IN BANGLADESH - Theerka. N. (CV. Fahr Publishing, 2024)
This study investigates the disparities in water sanitation and its impact on public health in rural and urban areas of Bangladesh. Through a mixed-methods approach, combining both quantitative and qualitative data, the research examines access to clean water, sanitation practices, and the prevalence of waterborne diseases in both regions. The quantitative component involved surveying 500 households, revealing that 65% of rural households use unsafe water sources compared to 20% in urban areas. Additionally, 48% of rural households practice open defecation, significantly higher than the 12% in urban households. The qualitative data, gathered from 30 interviews and focus group discussions, revealed that rural participants are less aware of the health risks associated with poor sanitation and water quality. The study concludes that while urban areas benefit from better infrastructure and awareness, rural areas remain underserved, highlighting the need for improved sanitation infrastructure, community engagement, and public health education. The findings contribute to the global discourse on improving water and sanitation access, supporting the United Nations Sustainable Development Goal 6 for clean water and sanitation for all.